Foldameric β‐H18/20P Mixed Helix Stabilized by Head‐to‐Tail Contacts: A Way to Higher‐Order Structures. Issue 17 (3rd April 2013) - Szolnoki, Éva; Hetényi, Anasztázia; Mándity, István M.; Fülöp, Ferenc; Martinek, Tamás A.
Abstract: Peptidic foldamers are known to exhibit increased diversity in the periodic secondary‐structure space in comparison with their natural counterparts, but their higher‐order self‐organization has been studied less thoroughly. In theory, large‐diameter peptide foldamer helices have the capability of self‐recognition through axial helix–helix interactions (e.g., head‐to‐tail), but this phenomenon has previously been observed in only one instance. In this article we report on the discovery of the largest‐diameter β‐peptidic mixed helix to date, the H18/20 P helix. Its formation is solvent‐dependent and its folding occurs cooperatively through head‐to‐tail self‐assembly in solution. These findings suggest that axial helix–helix interactions can serve as a new mode for the formation of tertiary/quaternary structures for peptide foldamers, which also show higher‐order structural diversity than natural proteins. Abstract : The discovery of a large‐diameter β‐peptidic foldamer mixed helix is reported. The formation of the β‐H18/20 P helix is solvent‐ and concentration‐dependent, and occurs by a head‐to‐tail self‐assembly process in solution.